Sistem Kepercayaan Malim: Pandangan dan Identitas Batak Toba - Rugun Marsaulina S (Endogami: Jurnal Ilmiah Kajian Antropologi, 2021)
Malim is a belief that grew and originated from the Toba Batak. Hutatinggi is the center of Malim worship in Indonesia. The problem is how the Hutatinggi community views Malim and what is the shape of the identity of the Batak Toba, Malim and nonParmalim adherents. The views of the non-Parmalim Toba Batak people accept this belief with open eyes even though from a Christian perspective it is not in accordance with the practice of Jesus and this belief has various rituals. The identity that can be seen directly and differentiates Parmalim from the Toba Batak people in general in Hutatinggi is in terms of the clothes they wear, namely their habit of wearing sarongs in everyday life and the use of white cloth rolled up to the head for men. So the identity for Malim is their belief in the owner of the Malim kingdom, social organizations, and Malim rituals. Belief in Debata Mulajadi Nabolon as the creator of the heavens and the earth and the rituals of worshiping beliefs ranging from Mararisabtu to Sipaha Sada and Sipaha Lima which are categorized as prioritized cultural attributes through the internalization process of values, goals and ideas.